2021
DOI: 10.1371/journal.pgen.1009845
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analyses of light-regulated genes in Aspergillus nidulans reveal a complex interplay between different photoreceptors and novel photoreceptor functions

Abstract: Fungi sense light of different wavelengths using blue-, green-, and red-light photoreceptors. Blue light sensing requires the “white-collar” proteins with flavin as chromophore, and red light is sensed through phytochrome. Here we analyzed genome-wide gene expression changes caused by short-term, low-light intensity illumination with blue-, red- or far-red light in Aspergillus nidulans and found that more than 1100 genes were differentially regulated. The largest number of up- and downregulated genes depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…WC proteins have been described in most fungi together with other photoreceptors like phytochromes, cryptochromes, and rhodopsins [ 12 , 13 ]. In Aspergillus nidulans , WC proteins interact with the phytochrome in a light sensing complex capable of sensing red light (phytochrome) and blue light (WC proteins) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…WC proteins have been described in most fungi together with other photoreceptors like phytochromes, cryptochromes, and rhodopsins [ 12 , 13 ]. In Aspergillus nidulans , WC proteins interact with the phytochrome in a light sensing complex capable of sensing red light (phytochrome) and blue light (WC proteins) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…intensity of UV radiation, temperature, or consequences of elevated temperature such as decreased humidity. Genome-wide transcription studies demonstrated that large groups of genes are controlled by this important environmental factor (Rosales-Saavedra et al 2006 ; Chen et al 2009 ; Fuller et al 2013 ; Bayram et al 2016 ; Tagua et al 2020 ; Yu et al 2020 , 2021 ). Light of different wavelengths can regulate germination, vegetative growth, asexual and sexual development, stress responses, pathogenic or symbiotic relationships, metabolism including mycotoxin production and circadian rhythm in fungi (Ruger-Herreros et al 2011 ; Yu and Fischer 2019 ; Díaz and Larrondo 2020 ; Schumacher and Gorbushina 2020 ), and these observations should always be taken into consideration in any illuminated fungal cultures.…”
Section: Fungi and Lightmentioning
confidence: 99%
“…It is important to note that fungi can differentiate between less and more red shifted (e.g. λ ≅ 700 nm and λ ≅ 760 nm) illumination with marked alterations in conidiogenesis, germination of conidia, and even in illumination-responsive changes in global gene expression patterns (Yu et al 2021 ). In order to facilitate the shift towards the near-infrared spectrum in microscopic techniques used in Mycology, the scope of on-going and future fungal physiological, developmental, and omics-based studies should be expanded to cover the near-infrared spectrum of light as well.…”
Section: Incorporation Of Red Far-red and Near-infrared Fluorescent P...mentioning
confidence: 99%
See 2 more Smart Citations